Competing Mechanisms for Photocurrent Induced at the Monolayer–Multilayer Graphene Junction. Issue 24 (16th May 2018) - Zhang, Youwei; Zheng, Hemei; Wang, Qiyuan; Cong, Chunxiao; Hu, Laigui; Tian, Pengfei; Liu, Ran; Zhang, Shi‐Li; Qiu, Zhi‐Jun
Abstract: Graphene is characterized by demonstrated unique properties for potential novel applications in photodetection operated in the frequency range from ultraviolet to terahertz. To date, detailed work on identifying the origin of photoresponse in graphene is still ongoing. Here, scanning photocurrent microscopy to explore the nature of photocurrent generated at the monolayer–multilayer graphene junction is employed. It is found that the contributing photocurrent mechanism relies on the mismatch of the Dirac points between the monolayer and multilayer graphene. For overlapping Dirac points, only photothermoelectric effect (PTE) is observed at the junction. When they do not coincide, a different photocurrent due to photovoltaic effect (PVE) appears and becomes more pronounced with larger separation of the Dirac points. While only PTE is reported for a monolayer–bilayer graphene junction in the literature, this work confirms the coexistence of PTE and PVE, thereby extending the understanding of photocurrent in graphene‐based heterojunctions. Abstract : A novel laser thinning technique is adopted to produce uniform and low‐defect monolayer–multilayer graphene junctions. When exposed to different relative humidity, a separation of the Dirac points of the monolayer and multilayer graphene can be effectively controlled. The contributing photocurrent mechanism is thus found to rely on the mismatch of their Dirac points.